Monocytes in Neonatal Bacterial Sepsis: Think Tank or Workhorse? - Caitlin Doughty; Louise Oppermann; Niels-Ulrik Hartmann; Stephan Dreschers; Christian Gille; Thorsten Orlikowsky (MDPI AG, 2022)
Infection and sepsis remain among the leading causes of neonatal mortality. The susceptibility of newborns to infection can be attributed to their immature immune system. Regarding immune response, monocytes represent a numerically minor population of leukocytes. However, they contribute to a variety of immunological demands, such as continuous replenishment of resident macrophages under non-infectious conditions and migration to inflamed sites where they neutralize pathogens and secrete cytokines. Further functions include the presentation of antigens and T-cell activation. Cytokines coordinate host responses to bacterial and viral infections and orchestrate ongoing physiological signaling between cells of non-immune tissues. A critical event is the skewing of the cytokine repertoire to achieve a resolution of infection. In this regard, monocytes may hold a key position as deciders in addition to their phagocytic activity, securing the extinction of pathogens to prevent broader organ damage by toxins and pro-inflammatory reactions. Neonatal monocytes undergo various regulatory and metabolic changes. Thus, they are thought to be vulnerable in anticipating pro-inflammatory conditions and cause severe progressions which increase the risk of developing sepsis. Furthermore, clinical studies have shown that exposure to inflammation puts neonates at a high risk for adverse pulmonary, immunological and other organ developments, which may result in multiorgan disease. This review discusses significant functions and impairments of neonatal monocytes that are decisive for the outcome of bacterial infections.